Influence of Freshwater Discharges on Biogeochemistry and Benthic Communities of a Coral Reef Ecosystem (La Réunion Island, Indian Ocean) - Tedetti, Marc; Bigot, Lionel; Turquet, Jean; Guigue, Catherine; Ferretto, Nicolas; Goutx, Madeleine; Cuet, Pascale (Frontiers in Marine Science, 2020)
We investigated the influence of freshwater discharges on biogeochemistry and benthic communities of La Saline fringing reef, the largest coral reef system of La Réunion Island (France, Indian Ocean). Sampling was conducted in February-March 2012 along a land-ocean continuum, including rivers, groundwater, reef waters and oceanic waters. Our results indicated the discharges of basalt groundwater (enriched in nitrates) in the southern part of the reef, and the discharges of sand groundwater and river waters (enriched in organic matter) in sites located northward. These discharges mainly impacted fore reef surface waters, while groundwater resurgences were more diffuse and not clearly detected in depth. We highlighted the relationship Si(OH)4/NO3- to identify basalt groundwater discharges. We also put forward the relationships humic-like fluorescence/NH4+ and tryptophan-like fluorescence/PO43- to identify sand groundwater discharges and wastewater pollutions, respectively. We observed the eutrophication of the southern part of the reef through higher phytoplankton biomasses, a massive presence of fleshy algal formations and a low coral coverage. The spatial homogeneity of the benthic community structures onto the entire slope contrasted with the spatial heterogeneity of chemical variables in water. This reflected the different spatial and temporal scales involved in biological and chemical processes in coral reef ecosystems.